Only as a last resort: Sociocultural differences between women and men explain women's heightened reaction to threat, not evolutionary principles. (25th July 2022) - Huntsinger, Jeffrey R.; Raoul, Akila
Abstract: The target article proposed that women display greater self-protectiveness than men to major physical and social threats because such self-protective responses have higher fitness value for women than men. Rather than having evolutionary roots, we suggest the various physiological, behavioral, and emotional responses to social and physical threats exhibited more by women than men are instead rooted in sociocultural forces.